MOTIVATIONAL DRIVERS FOR WRITING AMONG UNIVERSITY STUDENTS IN ISLAMIC STUDIES - Siti Aishah, Chu Abdullah; Mohd Sham, Kamis; Mohd Nizam, Sahad (2024)
Motivation to write and share religious experiences is essential, especially in Islamic da’wah where preachers excel in verbal communication but write less. Both verbal and written proficiency are crucial for da’wah, making it important for students in Islamic studies to be motivated to write and share religious experiences and knowledge. Yet, there is limited understanding of their motivation for such writing purposes. Therefore, the objective of this study is to describe the students’ perceptions on the factors that motivate them to write. Using a qualitative approach, the study conducted interviews with students enrolled in Islamic studies in Universiti Malaysia Sarawak (UNIMAS). The results indicated that feedback significantly influenced students to enhance their writing skills, and various factors, including the choice of topics or genres, technology assistance, and support from lecturers, played essential roles in motivating them to write. Additional drivers, such as increased reading, positive mindset, writing opportunities, good intentions, and family support, were also identified. Based on these findings, the study recommends further investigation into the impact of a supportive writing environment on the writing motivation of university students in Islamic studies, particularly at UNIMAS, to enhance the effectiveness of such an environment.